2020
DOI: 10.1111/cico.12453
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Place and Feelings of Safety: Examining Young Adults’ Experiences of their Local Environment using Mobile Surveys

Abstract: This study aims to examine feelings of safety and the correlates to feelings of decreased worry toward crime within individuals' proximate environments. Data from adults living in Southeast Queensland (N = 72) were collected using a mobile application. Findings of a thematic analysis of these data suggest that safety perceptions are primarily driven by (a) physical features of the proximate environment, (b) social characteristics of a place, and (c) location familiarity or awareness. This study concludes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
(174 reference statements)
0
9
0
Order By: Relevance
“…Place vitality can also be reflected through music, games, shows and dances that enlivened a place, welcomed crowd gathering and provided a sense of security. Additionally, the gatherings increased community involvement that led to the positive perception of a place regarding safety (Chataway, 2020). As such, this study found that the female group had a higher preference for place vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Place vitality can also be reflected through music, games, shows and dances that enlivened a place, welcomed crowd gathering and provided a sense of security. Additionally, the gatherings increased community involvement that led to the positive perception of a place regarding safety (Chataway, 2020). As such, this study found that the female group had a higher preference for place vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Labhart et al, 2019) and outcomes (e.g. Chataway, 2019), this study aimed to unravel why participation varies within the sample. The statistical analyses revealed that being female, older and a criminology student generally increased the odds of greater participation.…”
Section: Feasibility Of Stunda and Implications For Future Researchmentioning
confidence: 99%
“…A recurring phenomenon in experience sampling studies is that compliance rates vary heavily within samples (e.g. Chataway, 2019; Labhart et al, 2019). An interesting question thus involves exploring participant characteristics between those answering many surveys and those answering a few.…”
Section: The Present Studymentioning
confidence: 99%
“…Since then, there has been a growth in similar studies using smartphone-based experience methods (e.g. Birenboim, 2016Birenboim, , 2018Chataway, 2019;Chataway et al, 2017;2019;Irvin-Erickson et al, 2020;; for a review, see . While based on small-scale studies of pilot character, this research shows that fear of crime can be studied as an everyday phenomenon using smartphone-based experience methods.…”
Section: Everyday Experience Methodsmentioning
confidence: 99%
“…Goldner et al, 2011). Although this methodology was mentioned in relation to fear of crime some time ago , it is not until recently that fear of crime research has come to employ this increasingly popular methodological approach by examining fear of crime as a dynamic feature that varies across space and time (Chataway et al, 2017(Chataway et al, , 2019Irvin-Erickson et al, 2020;; see also Chataway, 2019).…”
Section: Studying Experiential Fear Of Crimementioning
confidence: 99%